Pengaruh Perubahan Kurikulum terhadap Kinerja Mengajar Guru di SD Hj. Isriati Moenadi Ungaran (Studi Fenomenologi) - Farhan Saiful Ibrahim; Haryono Haryono (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2026)
This study aims to understand teachers’ experiences in responding to curriculum changes and their implications for teaching performance at SD Hj. Isriati Moenadi Ungaran. The focus is not only on policy transformation but also on how teachers interpret and adapt to these changes in instructional practice. A qualitative approach with a phenomenological perspective was employed. Data were collected through in-depth interviews, observations, and documentation, and subsequently interpreted using the Interpretative Phenomenological Analysis (IPA) approach. The findings indicate that curriculum changes are perceived as both challenges and opportunities. Teachers encounter difficulties in understanding new concepts and adjusting instructional tools. In addition, limited training and administrative demands affect their readiness. However, these conditions also encourage teachers to become more adaptive and creative in their teaching practices. The impact of these changes is reflected in the planning, implementation, and evaluation of learning. This study concludes that the success of curriculum implementation is strongly influenced by teachers’ ability to understand and adapt to change. Therefore, continuous professional development aligned with teachers’ real experiences is essential.